ANALISIS PENGARUH PROMOSI, WORD OF MOUTH, DAN BRAND AWARENESS TERHADAP PEMBENTUKAN MINAT BELI PADA COFFEE GROOVE SEMARANG - Safitri, Saptianipo Aprilia; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2015)
The purpose of the research is to analyze the impact of promotions, word of mouth and brand awareness regarding intention to buy at Coffee Groove Semarang. The subject of this research is Coffee Groove’s customer. Samples used in this research are 100 respondents with random sampling technique method. It’s used to collect data by survey with questionnaires. Technique that used in the research to get the result is multiple linear regression technique. Analyzing data by using a multiple linear regression’s technique, result shown is that Y = 0,328X1 + 0, 287X2 + 0,143X3. It interprets that the promotion, word of mouth, and brand awareness possess positive effect towards intention to buy. Because of the significant value of promotion and word of mouth is less than 0,05 and the significant value of brand awareness is more than 0,05 so, that can be concluded that there is effect of  promotion and word of mouth significantly related intention to buy at Coffee Groove Semarang and there is not the affect of brand awareness significantly towards intention to buy at Coffee Groove Semarang.